The gut microbiota, environmental factors, and links to the development of food allergy - Lee, Khui Hung; Song, Yong; Wu, W.; Yu, K.; Zhang, Guicheng (BMC, 2020)
Food allergy appears to have its roots in an insufficient exposure to a diverse range of environmental microbiota during early life. Microbial exposure ensures the colonization of the gastrointestinal tract with commensal microbes, which is necessary for the induction of a balanced and tolerogenic immune function. High-throughput sequencing technology has facilitated in-depth studies of the gut microbiota as well as bacterial-derived metabolites. Although the role of the microbiota in allergies is now widely studied, its importance for food allergy was only recently noted. Studies in human cohorts have shown that there is an association of dysbiosis and pathogenesis of food allergy, while studies from animal models have demonstrated the capacity of specific species in the gut microbiota to alter immune response, which may lead to the desensitization of food allergy. This article reviews the role of the gut microbiota in food allergy, and discusses the influence of environmental factors as well as prevention and management strategies relating to such regulatory mechanism.